2019
DOI: 10.1097/md.0000000000017362
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae-induced multiple invasive abscesses

Abstract: Rationale:Klebsiella pneumoniae infection can induce multiple invasive abscesses, and the invasive infection is severe and life-threatening.Patient concerns:A 69-year-old previously healthy Chinese male presented with fever, chill, backache, and ocular pain.Diagnosis:The blood culture results indicated Klebsiella pneumoniae of the K1 serotype. Multiple invasive abscesses in liver, lung, eye, soft tissue, and central nervous system were identified by imaging examination. Subsequently, the patient experienced ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…K . pneumonia can cause a severe infection, such as meningitis or brain abscess, and can be life-threatening which needs advanced antibiotics treatment [ 23 ]. The previous study explored endocervical culture from 100 women and they found Klebsiella pneumonia occupied 2% of the study women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…K . pneumonia can cause a severe infection, such as meningitis or brain abscess, and can be life-threatening which needs advanced antibiotics treatment [ 23 ]. The previous study explored endocervical culture from 100 women and they found Klebsiella pneumonia occupied 2% of the study women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In current practice, hypermucoviscosity KP serotype are diagnosed by string test. 1,2 The diagnosis may be confirmed by identifying capsular serotype via polymerase chain reaction assay. 1,2 Hypervirulent KP (hvKP) is defined by multiple organ localizations, in a few hours, very often in a healthy individual.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The diagnosis may be confirmed by identifying capsular serotype via polymerase chain reaction assay. 1,2 Hypervirulent KP (hvKP) is defined by multiple organ localizations, in a few hours, very often in a healthy individual. 1,2 Determination of hypervirulence is genetic and becomes frequent.…”
Section: Discussionmentioning
confidence: 99%
“…This is a rare clinical condition characterized by a primary liver abscess in combination with abscesses of other distant organ, including the eyes, lungs and central nervous system [4,5], and it most often occurs in patients with diabetes mellitus and hypertension [6]. The incidence of invasive K. pneumoniae liver abscess syndrome is high in Asia, and the prognosis is typically poor [7,8]. Prompt diagnosis and active treatment can improve the outcome.…”
Section: Introductionmentioning
confidence: 99%